Finite Element Stress Analysis of Airplane Seat - YAYLA, PAŞA (My University, 2021)
Finite element method (FEM) is frequently used in the seat industry, as well as in the aircraft seat industry,which is a sub-branch of it, especially in the last 10-15 years. Developments in finite element (FE) analysis haveenabled safer and cheaper designs to be created in the seat industry. The accuracy of the finite element analysisperformed while using this method is extremely important. For this reason, in creating the finite element model,some important parameters must be selected and processed correctly for the model to give the correct result.These parameters can be listed as element size, time scale, analysis type, and material model. The verificationof the Finite element analysis (FEA) results is usually done using experimental methods. It is known that in thefinite element analysis results almost equivalent to experimental results are obtained when the aforementionedparameters are modeled correctly. This study aims to perform static stress analysis and topology optimizationof an airplane seat using the FEM. The static stresses and displacements created at the seat are calculated undersimulated loading conditions. Thanks to the topology optimization study, the weight of the airplane seat isminimized by a 30% without sacrificing seat safety. A comparison of static stresses obtained from the FE andanalytical models indicates a reasonable correlation, demonstrating confidence in our FE analysis.